Diagnosing and Reporting of Occupational Diseases: An Assessment Study of Reports from an Italian Workplace Safety Prevention Program Service - Lecca, Luigi Isaia; Pili, Sergio; Lai, Michele; Murru, Alessandro; Campo, Giuseppe; Pizzuti, Antonio; Mattioli, Stefano; Campagna, Marcello (La Medicina del Lavoro, 2025)
Background: The criteria for diagnosing and compensating for occupational diseases vary significantly between countries. The lists of occupational diseases often include diagnostic and attribution criteria that are usually not very specific. As a result, the quality of occupational disease reports is frequently subpar. The aims of this study were to assess the quality of diagnosis and reporting, as well as to evaluate the causal link between reported occupational diseases and occupational risk factors. Methods: Four occupational physicians assessed the quality of diagnosis by blindly applying Spreeuwers’ performance indicators for diagnosis and reporting. Following Violante’s criteria, the four evaluators also tested the levels of evidence to evaluate the quality (and associated likelihood) of the diagnosis and the quality of exposure to occupational risk factors in a sample of 104 occupational disease reports, grouped by diagnosis and examined by the local Workplace Safety Prevention Service. Separate scores for each performance indicator and the Total Quality Score (TQS, ranging from 0 to 10), along with the progressive levels of evidence, were then assigned for each occupational disease report. Results: The mean TQS was below the threshold of sufficiency (6) emerged for 72% of the diagnoses, primarily including musculoskeletal disorders, pulmonary silicosis, and noise-induced occupational hearing loss. When applying Violante’s criteria for the level of evidence of the diagnosis, it was insufficient for 13.5% of the reported cases, while the level of evidence for exposure to occupational risk factors was deemed insufficient for 19% of the cases, and no cases demonstrated a level of evidence that was highly probable or nearly certain. Conclusions: Despite the overall quality of the reported cases of occupational diseases being reasonably good, improvements in the quality of diagnosis and reporting could be achieved through strict adherence to standardized diagnostic criteria and by training health personnel to collect data regarding occupational and non-occupational risk factors properly.